Genome-Wide Identification and Expression Analysis of GST Genes during Light-Induced Anthocyanin Biosynthesis in Mango (Mangifera indica L.) - Shiqing Yuan; Chengkun Yang; Bin Zheng; Junbei Ni; Kaibing Zhou; Minjie Qian; Hongxia Wu (Plants, 2024)
Anthocyanins are important secondary metabolites contributing to the red coloration of fruits, the biosynthesis of which is significantly affected by light. Glutathione S-transferases (GSTs) play critical roles in the transport of anthocyanins from the cytosol to the vacuole. Despite their importance, GST genes in mango have not been extensively characterized. In this study, 62 mango GST genes were identified and further divided into six subfamilies. MiGSTs displayed high similarity in their exon/intron structure and motif and domain composition within the same subfamilies. The mango genome harbored eleven pairs of segmental gene duplications and ten sets of tandemly duplicated genes. Orthologous analysis identified twenty-nine, seven, thirty-four, and nineteen pairs of orthologous genes among mango MiGST genes and their counterparts in Arabidopsis, rice, citrus, and bayberry, respectively. Tissue-specific expression profiling highlighted tissue-specific expression patterns for MiGST genes. RNA-seq and qPCR analyses revealed elevated expression levels of seven MiGSTs including MiDHAR1, MiGSTU7, MiGSTU13, MiGSTU21, MiGSTF3, MiGSTF8, and MiGSTF9 during light-induced anthocyanin accumulation in mango. This study establishes a comprehensive genetic framework of MiGSTs in mango fruit and their potential roles in regulating anthocyanin accumulation, which is helpful in developing GST-derived molecular markers and speeding up the process of breeding new red-colored mango cultivars.